Workload analysis using full time equivalent method for production operators at PT Pertamina EP Tambun Field - Heru Santosa; Siti Rahayu; Dodit Ardiatma (TEKNOSAINS : Jurnal Sains, Teknologi dan Informatika, 2025)
Workload is a major challenge in human resource management, especially in modern industrial environments. Workload imbalance between production operators can have a negative impact on productivity, operational efficiency, and employee welfare. This study aims to analyze the workload of operators using the Full Time Equivalent (FTE) method as an accurate approach. The results of the analysis show that all operators at the gathering station workstation experience excessive workload conditions, with FTE values ​​ranging from 1.285 to 1.389. In contrast, operators at the gas station and well and pipeline station show FTE values ​​within normal limits, namely between 1.013 and 1.028. This imbalance also affects the work performance of operators, especially at the gathering station, which shows a lower average performance value compared to other stations. As a solution, a recalculation of the workload was carried out after adding one operator each to each gathering station unit. The results showed that the FTE value was within the normal range, indicating an improvement in work distribution and the potential for increasing employee performance.